Open Versus Arthroscopic Treatment of Chronic Lateral Epicondylitis and Worker's Compensation - Laxminarayan Bhandari, M.D; Fadi Bouri, M.D; Tuna Ozyurekoglu, M.D (Elsevier, 2020)
Purpose: To compare the short-term outcomes between arthroscopic and open procedures for the treatment of lateral epicondylitis. Because a significant portion of patients have worker's compensation (WC), the outcomes in these subgroups were separately analyzed. Methods: A retrospective analysis of patients who had surgical treatment of lateral epicondylitis by a single surgeon from 2010 to 2017 was performed. Patients who were symptomatic after 9 months of conservative treatments including nonsteroidal medications, steroid injections, and physical therapy were offered surgical intervention. The type of surgery was selected after detailed consultation with the patient. Charts were reviewed for preoperative pain, grip strength as measured by dynamometer, smoking status, and WC status. Postoperative assessments included pain and grip strength at 6 weeks and time taken to return to full duty. Two groups were compared using unpaired t test and chi-squared tests. Results were compared with similar studies in the literature. Results: The study included 30 patients in the arthroscopic debridement group and 42 patients in the open tenotomy and reinsertion group. Eighteen patients (25%) had WC. Compared with the open group, the arthroscopic group had earlier return to full duty (mean 7.13 weeks, confidence interval [CI] 6.21 to 8.05 versu mean of 12.22 weeks, CI 11.21 to 13.24; P < .001) and less time for complete pain relief (mean 7.4 weeks, CI 7.02 to 7.93 versus 9.5 , CI 8.68 to 10.44; P = .043). No difference was seen among the groups in terms of unfavorable outcome (persistent pain and recurrence of pain), JAMAR hand dynamometer score at 6 weeks, and visual analog score at 6 weeks. A total of 11 patients (15%) had unfavorable outcome. Incidence of unfavorable outcomes was more in patients with WC insurance (36% in WC versus 7% in non-WC; P = .023). No association was seen with smoking status. WC patients also had a longer time to return to full duty (16.68 weeks for WC versus 7.65 weeks for non-WC; P < .001) and a longer time to get complete pain relief (12.4 weeks for WC versus 7.5 weeks for non-WC; P < .001). Conclusion: The arthroscopic technique offers advantages of earlier return to work and shorter recovery period along with additional advantages of joint inspection and ability to treat coexisting pathologies. WC patients had a longer time to return to full duty and time for complete pain relief. Level of Evidence: Level III, retrospective comparative study.